Unveiling Meanings in Skin 1004 Advertisements - Dewa Ayu Anggan Dina Satrisna; Ni Nyoman Deni Ariyaningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This research analyzes the semiotic elements in SKIN1004 product advertisements, focusing on verbal and non-verbal signs in TEA-TRICA Purifying Toner, TEA-TRICA Relief Ampoule, and TEA-TRICA BHA Foam advertisements. This research seeks the hidden meaning conveyed in advertisements using Barthes's (1967)theory of meaning and Wierzbicka's (1996) color theory. The data was collected from SKIN 1004's official Instagram account. The results show that SKIN1004's advertisements use a combination of verbal cues, such as product names and text, as well as non-verbal cues, such as colors and design elements, to demonstrate product advantages and attract customers. They strategically symbolize purity, natural ingredients, and nature, the color green. This is in line with the brand image and function of the product.